Geographic Variation in the Acoustic Signals of Dendropsophus nanus (Boulenger 1889) (Anura: Hylidae) - Annibale, Fabiane S. [UNESP]; Sousa, Veronica T. T. de; Silva, Fernando R. da; Murphy, Christopher G. (Herpetologists League, 2020)
Anurans communicate information during breeding activity to eonspeeifics mainly through acoustic signals, and different evolutionary forces may produce geographic variation in such communication systems. To understand which variables influenced geographic variation in the advertisement call of Dendropsophus nanus, a generalist species with a broad distribution in South America, we tested three nonexclusive hypotheses: geographic distance, environ men till temperature, and body size. The advertisement call of this species consists of two note types: Type A, which functions in spacing among males in aggregations, and Type B, which may influence female choice. To determine the effect of the three explanatory variables on each note, we sampled nine populations in central and southern Brazil, We found that geographic distance and temperature were the main variables explaining variation in both notes. An exploratory analysis revealed, differences in the advertisement call between populations in western and eastern localities. Because temperature was spatially structured, geographic distance may have produced variation in temperature along the longitudinal gradient, resulting in the observed variation in bioacoustic parameters among populations. Also, we observed that individuals in warmer localities were smaller than those from colder localities, and this difference in body size was correlated to the note repetition rate of Type A notes. Our liridings indicate that variation in acoustic parameters may be an indirect result of temperature acting on body size. Thus, geographic variation in the advertisement call of D. nanus may be due to both neutral and selective processes.
Keywords: Bioacoustics; Evolutionary' forces; Intraspecific variation; Neutral pressures; Population ecology; Selective pressures